Nelson Monument - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
Vintage view of the Nelson Monument in Trafalgar Square, Bridgetown, Barbados. There’s a lamp post stationed in front of the monument. A lady is standing at the base of the monument, whilst a man is seen walking away from the monument. In the background what is known as a 1/4d horse drawn tram is seen. Men and women are also seen walking around in the vicinity of the monument. On the left-hand side of the monument there are a various horses and carriages. At the back of the postcard: Barbados Views – Copyright Knight & Co. No. 10. , AL INT £5-, 249202.
Landscape, Black & white, 5 1/2 x 3 1/2 inches.
Keywords: Historical markers; Cities and towns; Monuments and memorials; City and town life; Clothing and dress; Nelson Monument